Spatial Analysis of Modeling Potential Flood Areas in Padang City using Google Earth Engine - Yunika, Rahmi; Ashar, Faisal (Universitas Negeri Padang, 2024)
Flooding in Indonesia tends to increase from year to year, and one of the causes is high rainfall. Padang City is one of the areas that has high rainfall intensity which can trigger flooding. This research aims to present spatial information on flood-prone areas by processing data in Google Earth Engine (GEE) and determine the level of flood vulnerability in Padang City. GEE is a platform capable of processing geopatial data on a large scale using multi-temporal imagery and utilizing cloud computing technology that allows solving large problems in a short time. This research uses CHIRPS Dayli data: Climate Hazard Group Infrared Precipitation, NASA SRTM Digital Elevation 30 m, Sentinel 2-A and research administrative boundaries. This study uses rainfall, elevation, TPI, NDWI and NDVI parameters. Data analysis and processing in this study were fully carried out in GEE. The results showed that the area very prone to flooding has an area of 5569.46 ha or 8.03%. The prone area is 28064.57 ha or 40.46% and the non-prone area is 35726.20 ha or 51.51%. The results of this research are expected to help the government in flood mitigation in Padang City.